Clinical significance of serum miR-21 in breast cancer compared with CA153 and CEA - Gao, Jianjian; Zhang, Qingyun; Xu, Jianjun; Guo, Lijuan; Li, Xuefeng (Chinese Journal of Cancer Research, 2013)
Objective: MicroRNA-21 (miR-21) has been shown to be a key regulator of carcinogenesis. There were few reports about the comparison of serum miR-21 with conventional tumor markers. This study aimed to explore the diagnostic value of circulating miR-21 as a tumor marker in breast cancer (BC) and compare it with CA153 and carcinoembryonic antigen (CEA). Methods: Circulating miR-16 and miR-21 were amplified and quantitatively detected by real-time PCR in 89 BC patients and 55 healthy controls. The levels of CA153 and CEA were measured through electrochemiluminescence assays. Then the sensitivity in diagnosis of BC was compared among miR-21, CA153 and CEA. Results: The level of serum miR-21 was significantly higher in BC patients than controls (P